Antioxidant activity and phenolic compound content of fresh and frozen Pereskia aculeata Miller stem tea (Research, Society and Development, 2020)
Pereskia aculeata Miller, popularly known in Brazil as ora-pro-nóbis (OPN), is considered an unconventional food plant (UFP); for being rich in bioactive compounds it is commonly used in disease treatment and supplementation. The aim of this study was to determine the in vitro antioxidant activity (IC50(DPPH)), total phenolic content (TPC) and total flavonoid content (TFC) of teas (aqueous extracts) produced from the flour of Pereskia aculeata Miller stems, evaluating the influence of freezing storage at these parameters. The results presented in this study are unprecedented in the literature. The mean values found for IC50(DPPH), TPC and TFC were (589.34 ± 69.48 μg mL-1); (86.06 ± 16.37 mg AGE g-1) and (13.18 ± 3.56 mg RE g-1), respectively. These phenolic compounds appear to play a major role in the moderate antioxidant potential of this type of tea. Freezing the extracts over a period of three weeks did not produce statistically significant changes in the above mentioned parameters. However, storage of this tea for a longer period is likely to cause such changes.